Remembering the Future - Berio, Luciano 1925-2003 (Cambridge, Massachusetts Harvard university press, 2006)
In Remembering the Future Luciano Berio shares with us some musical experiences that "invite us to revise or suspend our relation with the past and to rediscover it as part of a future trajectory." His scintillating meditation on music and the ways of experiencing it reflects the composer's profound understanding of the history and contemporary practice of his art.There is much in this short book that provides insight on Berio's own compositions. Indeed, he comments that writing it "led me to formulate thoughts that might otherwise have remained concealed in the folds of my work." He explores themes such as transcription and translation, poetics and analysis, "open work," and music theater. The reader will also find here numerous insights on the work of other composers, past and present, and much more. A figure of formidable intellect, Berio ranges easily among topics such as Schenkerian analysis, the criticism of Carl Dahlhaus and Theodor Adorno, the works of his friends and sometime collaborators Italo Calvino and Umberto Eco. But Berio carries his learning lightly--his tone is conversational, often playful, punctuated by arresting aphorisms: "The best possible commentary on a symphony is another symphony."
The Charles Eliot Norton Lectures
Keywords: Musical analysis